Chứng minh:
Biến đổi tương đương, ta có:
\(a^4+b^4\ge a^3b+ab^3\Rightarrow a^4-a^3b+b^4-ab^3\ge0\)
\(\Rightarrow a^3\left(a-b\right)-b^3\left(a-b\right)\ge0\Rightarrow\left(a^3-b^3\right)\left(a-b\right)\ge0\)
\(\Rightarrow\left(a^2-ab+b^2\right)\left(a-b\right)\left(a-b\right)\ge0\Rightarrow\left(a^2-ab+b^2\right)\left(a-b\right)^2\ge0\)
\(\Rightarrow\left(a^2-2a\frac{b}{2}+\left(\frac{b}{2}\right)^2+\frac{3}{4}b^2\right)\left(a-b\right)^2\ge0\)(luôn đúng)
\(\Rightarrow\)đpcm
ủa mà bạn ơi, Hằng đẳng thức a^3-b^3 là (a-b)(a^2+ab+b^2) mà
bạn bị lộn HĐT nên kết quả ra sai r kìa
mik nghĩ v, bạn xem lại nha